Nurturing Writing Confidence: A Case Study on the Effects of Free Writing in an EFL Classroom - Erza Delfira; Asbar, Asbar; Umiyati Jabri; Ismail, Ismail (Universitas Cokroaminoto Palopo, 2025)
This case study investigates the impact of free writing activities on students' confidence in writing English as a Foreign Language (EFL). Conducted at SMPN 5 Anggeraja with 20 students, the study examines how the integration of free writing influences students' writing confidence, comfort with writing tasks, perceptions of their writing abilities, and reduction in writing anxiety. Data was collected through semi-structured interviews conducted after three free writing sessions, which were observed by the researcher across 16 classroom meetings. The findings revealed that free writing significantly improved students' confidence in writing, as many students felt freer to express their ideas without the pressure of grammatical accuracy. Additionally, the study found that students became more comfortable with writing tasks, with 17 out of 20 students reporting increased engagement in writing activities. Students also reported enhanced perceptions of their writing abilities, with many expressing improved fluency and organization. Furthermore, a majority of students experienced a reduction in writing anxiety, as they began to approach writing tasks with greater ease. These findings suggest that free writing is an effective method for fostering writing confidence and reducing anxiety in EFL classrooms. The study underscores the importance of providing students with opportunities for low-pressure writing activities that prioritize content and self-expression over grammatical accuracy.